Environmentally Friendly Synthesis, Bioactivity Evaluation and Multi-Faceted Characterization of Bis (5-((1H-Imidazol-4-yl) Methyl) -3- Phenylimidazolidin -4- One) Derivatives - Dalaf, Adil Hussein; Saleh, Jamil Nadhem; Saleh, Mohammed Jwher; Talluh, Abdul Wahed Abdul Sattar (American Journal of Biomedicine and Pharmacy, 2024)
The ecologically friendly synthesis of imidazolidinone derivatives using conventional and microwave-assisted techniques is the main emphasis of this work. The broad-spectrum biological activity of imidazole-based compounds is widely known, yet there are currently no effective or sustainable production techniques available. The research included the preparation of new imidazole derivatives by reacting prepared Schiff bases with the amino acid histidine in the presence of ethanol as a solvent. The reaction was carried out using conventional and microwave methods, and the progress of the reaction was monitored and described by determining the melting point and purity. The Rf values ​​were determined using thin-layer chromatography (T.L.C.), infrared spectroscopy (FT-IR), proton nuclear magnetic resonance (1H-NMR), and quantitative elemental analysis (C.H.N.). The biological activity of the synthesized compounds was evaluated by examining their effect on the growth of four antibiotic-resistant bacterial isolates: Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus). The antibiotic Amoxicillin was used as a control sample. The prepared compounds showed good inhibitory activity against the tested bacteria.